Proceedings of the ACM/SIGDA International Symposium on Field Programmable Gate Arrays 2013
DOI: 10.1145/2435264.2435287
|View full text |Cite
|
Sign up to set email alerts
|

Heracles

Abstract: This paper presentsHeracles, an open-source, functional, parameterized, synthesizable multicore system toolkit. Such a multi/many-core design platform is a powerful and versatile research and teaching tool for architectural exploration and hardware-software co-design. The Heracles toolkit comprises the soft hardware (HDL) modules, application compiler, and graphical user interface. It is designed with a high degree of modularity to support fast exploration of future multicore processors of different topologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 22 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…From all the flow optimisation works for heterogeneous digital systems design found in literature [15][16][17][18][19][20][21], Highly Agile Masks Made Effortlessly from RTL (HAMMER) [22] is one of the projects closest to our work, as it focuses on workflow automation. It is used within the Chipyard framework [23] to automate its Very Large Scale Integration (VLSI) design flow.…”
Section: Related Workmentioning
confidence: 99%
“…From all the flow optimisation works for heterogeneous digital systems design found in literature [15][16][17][18][19][20][21], Highly Agile Masks Made Effortlessly from RTL (HAMMER) [22] is one of the projects closest to our work, as it focuses on workflow automation. It is used within the Chipyard framework [23] to automate its Very Large Scale Integration (VLSI) design flow.…”
Section: Related Workmentioning
confidence: 99%
“…From the result of hardware utilization, we found that the size of the hardware generated from the converted Verilog HDL code by the translation tool is practicable. For example, Heracles [11], that is an RTL based many-core simulation environment, implements a similar many-core processor to our processor. Its node mainly consists of a 7stage pipelined 32-bit MIPS processor core, instruction/data caches, and virtual channel NoC router.…”
Section: Evaluation Of Simulation Speedmentioning
confidence: 99%
“…Its node mainly consists of a 7stage pipelined 32-bit MIPS processor core, instruction/data caches, and virtual channel NoC router. In [11], in spite of using of hand-written Verilog HDL design methodology and a Virtex-6 LX550T FPGA which has 10% more slices than our targeted FPGA, the authors could implement an at most 25-node many-core processor because of its core complexity, whose node has a 32 KB local memory. Compared with that, our processor core is simpler but ArchHDL are able to generate a many-core processor with about twice core counts instead.…”
Section: Evaluation Of Simulation Speedmentioning
confidence: 99%